Identification, relationship and population status of sharks and rays landed at Rigaih Fishing Port as an effort of genetic conservation to endangered biota - Samsul Bahri; Hafinuddin Hafinuddin (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2023)
Aceh Jaya is one of the potential habitats and migration areas for various types of sharks because of its geographical location directly facing the Indian Ocean. This research was conducted to contribute to shark data collection through molecular genetic approaches. The objectives of this research include: conducting molecular identification of the types of sharks found; Analyzing the kinship relationships of the types of sharks found, and determining the conservation status of the types of sharks found. The results of the research that has been carried out found 6 individuals of sharks and 4 individuals of rays from 6 species of IU and 2 species of rays landed at Rigaih Fishing Port. The results of molecular identification show similarities with morphological identification results with an average percentage of per. ident reaching more than 95% and query cover more than 85%. The results of phylogenetic analysis show that the types of Sphyrna lewini and Rhynchobatus australiae have plesiomorphic characters. Based on references to the IUCN Red List standard unit, it shows that there are 3 species of sharks landed at Rigaih Fishing Port with critical status (CR), 4 species with vulnerable status (VU), and one species with near extinction status (NT). This result is an important finding where so far the status of shark populations landed and traded at Rigaih Fishing Port is unknown and has not been recorded statistically.